Reduced Alcohol Seeking and Withdrawal Symptoms in Mice Lacking the BDNF Receptor SorCS2 - Olsen, Ditte; Kaas, Mathias; Lundhede, Jesper; Molgaard, Simon; Nykjær, Anders; Kjolby, Mads; Østergaard, Søren D.; Glerup, Simon (Frontiers in Pharmacology, 2019)
Alcohol use disorder (AUD) is characterized by repetitive and uncontrolled intake of alcohol with severe consequences for affected individuals, their families and society as a whole. Numerous studies have implicated brain-derived neurotrophic factor (BDNF) activity in the neurobiology underlying AUD. The BDNF signaling mechanism is complex and depends on two receptor systems, TrkB and p75NTR, which appear to have opposite effects on alcohol seeking behavior in animal models. We recently discovered that the sortilin-related receptor SorCS2 forms complexes with both TrkB and p75NTR and is important for BDNF activity in the developing and adult CNS. Moreover, the SORCS2 gene was recently identified as the top association signal for severity of alcohol withdrawal symptoms. Hence, we speculated that SorCS2 deficient mice would have an altered response to alcohol. The role of SorCS2 in the acute and adapted response to alcohol was therefore investigated by comparing SorCS2 knockout (Sorcs2-/-) mice to wild type (WT) mice in three paradigms modeling alcohol sensitivity and consumption; alcohol-induced conditioned place preference, two-bottle choice test as well as the behavioral response to alcohol withdrawal. We found that, when compared to the WT mice, I) Sorcs2-/- mice displayed complete lack of alcohol-induced place preference, II) when given free choice between water and alcohol, Sorcs2-/- mice consumed less alcohol, and III) Sorcs2-/- mice showed no handling-induced convulsion in response to alcohol withdrawal following extended alcohol exposure. Taken together, these results show that lack of the alcohol withdrawal risk gene Sorcs2 results in abnormal behavioral response to alcohol in mice. Consequently, SorCS2 may play an important role in the molecular pathways underlying AUD and complications associated with alcohol withdrawal